Doświadczenia emocjonalne rodziców dzieci z autyzmem - Szmania, Lidia (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2014)
The purpose of this article is to compare the theoretical knowledge with parents' declarations concerning their emotional experiences resulting from the fact of having a child with autism. Main effort was made to indicate factors that affect these experiences, giving them a positive or negative meaning. Understanding the experiences that the parents of children with autism are highly probable to come across is extremely important as it can contribute to designing better supporting system for such families. It can also enhance mothers' and fathers' life satisfaction and increase effectiveness of preventive measures against the burnout phenomenon.